Faktor – Faktor yang Mempengaruhi Ekspor Lada Indonesia - Aryani, Firli; Sentosa, Sri Ulfa (Universitas Negeri Padang, 2023)
This study examines the effect of pepper production, household consumption, pepper export prices, and exchange rates on Indonesian pepper exports. The data used uses time series data for the period 1990 to 2019.The results of the study using multiple regression analysis using the OLS (Ordinary Least Square) method show that: (1) pepper production has a positive and significant effect on Indonesian pepper exports, domestic consumption has a negative and significant effect on Indonesian pepper exports, pepper export prices have a positive influence. but not significant to Indonesia's pepper exports, the exchange rate has a negative but not significant effect on Indonesian pepper exports.